STOCK VALUATION OF PT SEMEN BATURAJA TBK - Martha, Atrios
PT. Semen Baturaja Tbk is a company owned by the Government of the Republic of Indonesia with a majority share of 75.51%. PT Semen Baturaja Tbk officially registered shares on the Indonesian stock exchange in 2013 by issuing new shares or Initial Public Offering (IPO) with SMBR share code. The cement industry's performance is projected to increase more in 2019 compared with 2018. This is due to the government's efforts to continue to create a conducive business climate. In the property sector the government focuses on building houses with a target of 1,250,000 homes. The government is also encouraging housing development for ASN, TNI and Polri which will be recorded in the achievement of the Million Houses program. In 2020, the government is targeting to build 600 km of toll roads. In addition, 500 km of non-toll roads will also be built. The plan is expected to boost consumption of the national cement industry. Since July 2018, trending stock price of PT Semen Baturaja (SMBR) on the Indonesian stock exchange tends to decline, while other companies producing cement such as PT Semen Indonesia, PT Holcim Indonesia and PT Indocement Tunggal Prakarsa tend to fluctuate with trending rising. This final project will conduct research on PT Semen Baruraja Tbk's stock valuation, and will be written from an investor's point of view. The objectives of this final project are identifying internal and external analyzes which affect the company's stock performance, evaluating the intrinsic price of SMBR stock whether the stock is undervalued or overvalued and providing investment recommendation for investors whether to buy, hold or sell SMBR’s stock. The external analysis consists of global and national macroeconomic condition, condition of the cement industry and SWOT analysis. Internal analysis is carried out using the financial ratio analysis method. Based on external and internal analysis, stock price valuation is carried out. An investor's recommendation will be the outcome of stock price valuation. Absolute valuation is used to assess the target price of the firm's stock price. The phrase "absolute valuation" refers to the business valuation approach that uses Discounted Cash Flow (DCF) analysis to determine a firm's fair value. The evaluation results performed in this research show that SMBR stock price is overvalued. Using the discounted cash flow method, the intrinsic value per share of SMBR is negative IDR 78 per share, very far below market prices of IDR 486 per share by difference IDR 564 per share lower. The results of the sensitivity analysis show a change in the value of the components that affects the intrinsic value per share (beta, risk-free rate, interest rate, tax rate and terminal growth) by a few percent, changes in intrinsic value per share without significant differences. Target price for SMBR stock is less than 15% from market price, market prices of SMBR stock is IDR 486 per share as December 3, 2019, the SMBR stock target price negative IDR 75 per share. Based on those results, the final recommendation to investors is to sell SMBR stock.